2021
DOI: 10.28945/4867
|View full text |Cite
|
Sign up to set email alerts
|

Interest, Burnout, and Drop-Out Intentions Among Finnish and Danish Humanities and Social Sciences PhD. Students

Abstract: Aim/Purpose: This study focused on advancing understanding of individual variations in doctoral students’ interest in their doctoral studies and how they related to experiences of burnout and drop-out intentions in Denmark and Finland. Background: Ph.D. students’ experiences of interest, burnout, and dropout intentions among Finnish and Danish Ph.D. students have not been researched before. Research with a person-centred approach exploring individual variations in students undertaking doctoral studies in two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
1
12
0
Order By: Relevance
“…Several studies have reported high rates of university withdrawal intentions, for example, 30–70% of doctorate students will may not complete their PhD degree 8 , 29 31 . Experiences of high stress, anxiety and exhaustion, demonstrated a lack of interest in their studies which appears to influence drop-out intentions 8 , 32 , 33 . In contrast, satisfaction and engagement in research, supervision from several supervisors, integration and networks in the research community has a reverse effect in reducing burnout rates and enhancing success to degree completion 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported high rates of university withdrawal intentions, for example, 30–70% of doctorate students will may not complete their PhD degree 8 , 29 31 . Experiences of high stress, anxiety and exhaustion, demonstrated a lack of interest in their studies which appears to influence drop-out intentions 8 , 32 , 33 . In contrast, satisfaction and engagement in research, supervision from several supervisors, integration and networks in the research community has a reverse effect in reducing burnout rates and enhancing success to degree completion 34 , 35 .…”
Section: Discussionmentioning
confidence: 99%
“…It can be observed that success expectancy, as well as the intrinsic and utility values of the doctoral course, had stronger correlations with burnout dimensions than the attainment and cost values; candidates who thought they were good at doing their research and who had greater intrinsic and utility values were the least emotionally drained by their doctoral course. It could be argued that the high central tendency of the intrinsic and utility values in Algerian doctoral students could be justified by high interest profiles, development and impact interest profiles (Cornér et al, 2021), and the scarcity of Ph.D. positions in national contests. The associations are in line with the claim that graduate students' enrolment choices are undeniably based on the employment prospects of the course (Gedye et al, 2004) and that enjoyment of the course is associated with academic self-control (Gallaa et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Significant positive associations and predictive relationships were found between the components of the expectancy-value model and university students' metacognitive skills (Sellali & Yahiaoui, 2021). In their study, Cornér et al (2021) reviewed the literature on the possible motives that stem from doctoral students' interest in completing a doctoral course, and the most prevalent reasons were driven by intrinsic motives such as the understanding and the creation of knowledge, professional development, increasing job opportunities, and getting a raise or a better salary (Guerin et al, 2015;Neves, 2018;Pyhältö et al, 2020;Skakni, 2018;Stubb et al, 2012)…”
Section: Expectancy-valuementioning
confidence: 99%
“…The changes are also visible in quality assurance agendas, such as the mandatory courses in doctoral supervision for doctoral supervisors, which increasingly include modules on career guidance and talent development (Kobayashi, Godskesen, & Wichmann-Hansen, 2017). The complexity and many-sided expectations to the PhD and doctoral education have been reported to be confusing for doctoral students and supervisors, whose expectations and strategies are not always aligned with each other and with the wider institutional system framing doctoral education (Bengtsen, 2017;Cornér et al, 2018). The tensions can also be seen on the micro-level in the ways doctoral supervision and pedagogy has a complex, layered, and not always internally coherent expression and outcome (Bengtsen, 2016).…”
Section: Institutional Tensions -And New Responsibilities In Research?mentioning
confidence: 99%